2014
DOI: 10.1007/s10461-014-0976-8
|View full text |Cite
|
Sign up to set email alerts
|

“Was it a Mistake to Tell Others That You are Infected with HIV?”: Factors Associated with Regret Following HIV Disclosure Among People Living with HIV in Five Countries (Mali, Morocco, Democratic Republic of the Congo, Ecuador and Romania). Results from a Community-Based Research

Abstract: This study examined regret following HIV serostatus disclosure and associated factors in under-investigated contexts (Mali, Morocco, Democratic Republic of the Congo, Ecuador and Romania). A community-based cross-sectional study was implemented by a mixed consortium [researchers/community-based organizations (CBO)]. Trained CBO members interviewed 1,500 PLHIV in contact with CBOs using a 125-item questionnaire. A weighted multivariate logistic regression was performed. Among the 1,212 participants included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…This is a major issue in many countries, and in Morocco in particular, where HIV-infected individuals (but also other specific groups at risk of HIV transmission, including MSM and drug users) suffer from HIV-based discrimination [22]. Knowledge about the confidentiality of HIV testing results is therefore the primary lever to use when proposing HIV screening to at-risk populations.…”
Section: Resultsmentioning
confidence: 99%
“…This is a major issue in many countries, and in Morocco in particular, where HIV-infected individuals (but also other specific groups at risk of HIV transmission, including MSM and drug users) suffer from HIV-based discrimination [22]. Knowledge about the confidentiality of HIV testing results is therefore the primary lever to use when proposing HIV screening to at-risk populations.…”
Section: Resultsmentioning
confidence: 99%
“…It is, therefore, important that both be made aware of their rights and obligations as they pertain to HIV status disclosure. Henry et al (2015) argued that disclosure targets, as well as the time, place, and conditions under which disclosure occurred, should always be freely chosen by PLWH and, thus, an increased awareness of the voluntary nature of disclosure to HCP was imperative. This is particularly important in light of the fact that, in recent years, research has demonstrated how ART, when used correctly, can dramatically reduce heterosexual transmission rates (Loutfy et al, 2013;Vernazza, Hirschel, Bernasconi, & Flepp, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a study conducted in the United Kingdom, almost half of the PLWH who reported having experienced discrimination indicated that this discrimination involved a health care provider (Elford, Ibrahim, Bukutu, & Anderson, 2008). These kinds of experiences are highly detrimental to the mental and physical well-being of PLWH as manifested in increased psychological distress, poorer treatment adherence, and lower retention in care (Henry et al, 2015;Langebeek et al, 2014;Stutterheim et al, 2009).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The advantages of disclosure include safer sex, better (mental) health, more social support, and increased adherence to antiretroviral therapy [7][8][9], whereas the negative aspects of disclosure can include rejection, loneliness, stigma and discrimination [10].…”
Section: Introductionmentioning
confidence: 99%